Association of Arg194Trp, Arg280His and Arg399Gln Polymorphisms in X-ray Repair Cross-Complementing Group 1 Gene and Risk of Differentiated Thyroid Carcinoma in Iran - Fard-Esfahani, Pezhman (Pasteur Institute of Iran, 2011)
Background: X-ray repair cross-complementing group 1 (XRCC1) gene is a DNA repair gene and its non-synonymous single nucleotide polymorphisms (SNP) may influence DNA repair capacity which has been considered as a modifying risk factor for cancer development. Methods: A case-control study was conducted to investigate impact of three frequently studied polymorphisms (Arg194Trp, Arg280His and Arg399Gln) on developing differentiated thyroid carcinoma (DTC). Results: Increased risks for DTC were shown in homozygous (odds ratio [OR]: 3.66, 95% confidence interval [CI]: 0.38-35.60) and in dominant trait (OR: 1.22, 95% CI: 1.64-2.32) of Arg194Trp genotype. Also, for Arg280His genotype, an increased risk for DTC was shown in dominant trait (OR: 1.42, 95% confidence interval [CI]: 0.76-2.68), while a mildly reduction of risk for DTC (OR: 0.77, 95% [CI]: 0.50-1.17) was estimated in dominant Gln genotype of Arg399Gln. Considering combinatory effects of Arg194Trp and Arg280His genotypes on DTC, the calculated OR and 95% CI for being heterozygous for one of Arg194Trp or Arg280His genotypes were 1.57 and 0.90-2.74, respectively. Conclusion: Genotyping of codons 194, 280 and 399 in XRCC1 gene may use in risk assessment of DTC.